Development to Academic Achievement in Geography a Using of Multimedia Set for Grade 4 Students at Thammasat Primary School - Vongkham, Benyapa; Thanachaiworaphan, Waranit (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The development of academic achievement in geography by using of multimedia set which was a media to assist students in creating knowledge and understanding through hands-on activities. The objective is to study to academic achievement in geography using the media set by comparing the scores before and after learning of fourth-grade students at Thammasat Thammasat Primary School. Methodology: The study sample consists of fourth and sixth-grade students in the first semester of the 2023 academic year, totaling 35 students, selected using group randomization. The tools used for data collection include: 1) media set with an index of conformity ranging from 0.67 to 1.00. 2) Lesson plans for geography in grades 4/6, totaling 5 plans, with an index of conformity for learning management ranging from 0.67 to 1.00. 3) achievement test in geography with 20 questions, and an index of conformity ranging from 0.67 to 0.89. The experimental design involves using a single-group experimental design. The statistical methods employed include the mean and standard deviation. Results: The research findings indicate that the learning outcomes in geography, using the integrated media set, resulted in significantly higher post-learning scores compared to pre-learning scores, with statistical significance at the 0.01 level. The media set for geography learning management effectively promotes students' enthusiasm and participation in learning, leading to higher academic achievement. Conclusion: The study underscores the positive impact of integrating media sets in geography education, demonstrating a significant enhancement in learning outcomes. The observed increase in post-learning scores, coupled with heightened enthusiasm and participation, highlights the effectiveness of the media set in promoting academic achievement among students.